2022
DOI: 10.1017/s0007114522002616
|View full text |Cite
|
Sign up to set email alerts
|

Triangulating evidence for the causal impact of single-intervention zinc supplement on glycaemic control for type 2 diabetes: systematic review and meta-analysis of randomised controlled trial and two-sample Mendelian randomisation

Abstract: Although previous studies suggested the protective effect of zinc for type-2 diabetes (T2D), the unitary causal effect remains inconclusive. We investigated the causal effect of zinc as a single intervention on glycemic control for T2D, using a systematic review of RCTs and two-sample Mendelian randomization (MR). Four primary outcomes were identified: fasting blood glucose/fasting glucose, HbA1c, HOMA-IR, and serum insulin/fasting insulin level. In the systematic review, four databases were searched from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 93 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…Appropriate management procedure for malnutrition in diabetes mellitus patients has not still been established. Zn [130,131], vitamin E [132], folate [133], and L-arginine [134,135] supplementation and fiber-rich diets [136] have been suggested to potentially improve blood glucose control and insulin resistance. The reason why L-arginine improved glycemic control and insulin resistance is not clear in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate management procedure for malnutrition in diabetes mellitus patients has not still been established. Zn [130,131], vitamin E [132], folate [133], and L-arginine [134,135] supplementation and fiber-rich diets [136] have been suggested to potentially improve blood glucose control and insulin resistance. The reason why L-arginine improved glycemic control and insulin resistance is not clear in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc (Zn) [130,131], vitamin E [132], folate [133], and L-arginine [134,135] supplementation and fiber-rich diets [136] may improve glycemic control and insulin resistance (IR) in type 2 diabetes mellitus patients. The Mediterranean diet may improve glycemic control [137] and reduce cardiovascular diseases risk [137,138].…”
Section: Diabetes and Nutritionmentioning
confidence: 99%
“…Appropriate management procedure for malnutrition in diabetes mellitus patients has not still been established. Zn [131,132], vitamin E [133], folate [134], and L-arginine [135,136] supplementation and fiber-rich diets [137] have been suggested to potentially improve blood glucose control and insulin resistance. The reason why l-arginine improved glycemic control and insulin resistance is not clear in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc (Zn) [131,132], vitamin E [133], folate [134], and L-arginine [135,136] supplementation and fiber-rich diets [137] may improve glycemic control and insulin resistance (IR) in type 2 diabetes mellitus patients. The Mediterranean diet may improve glycemic control [138] and reduce cardiovascular diseases risk [138,139].…”
Section: Diabetes and Nutritionmentioning
confidence: 99%
“…Studies like the UK Biobank (UKB) have measured participants' self-reported exposure to many pharmacological compounds (6), such as prescribed and/or over-the-counter medication use, or vitamin supplementation use. These data enable an alternative drug-target MR approach, in which genome-wide significant variants associated with the target respective behavioral proxy are used instead of cis-variants (7). Since these phenotypes are generally cheaper to measure than biomarker or protein expression data, they may allow for larger sample sizes and potentially more powerful analyses (8).…”
Section: Introductionmentioning
confidence: 99%